Public Sphere, Rationality and the Limits of the Federal Experiment in Ethiopia - Fasil Merawi (Cхід, 2019)
In the multiethnic polity of Ethiopia, the practical realization of federalism in Ethiopia has been characterized by ethnic conflicts, manufacturing of difference and the abandoning of the grand narrative of Ethiopian unity. In this paper, using the notion of a public sphere as a space for public discourse and rationality from critical theory, I argue that the federal experiment in Ethiopia could only grow in the background of a public sphere that sustains a critical societal practice. Ethiopians could only engage in a common quest for societal progress and refinement, when they have a free and autonomous public sphere.  This space serves as a platform for reflecting on the contradictions in Ethiopian modernity and also existential problems in the country. Such an effort to evolve a public sphere as a foundation for democracy could have foundations in the different precursors of Ethiopian modernity like Dekike Estifanos, hatata of Zera Yacob and writings of Negadras Gebrehiwot and Hiruy Woldeselassie. It could also be situated on new forms of public sphere like social media and their role in fostering democracy in Ethiopia.